Born globals through knowledge-based dynamic capabilities and network market orientation - Diego Monferrer; Andreu Blesa; María Ripollés Meliá (BRQ Business Research Quarterly, 2015)
This paper studies the influence of network market orientation on Spanish born globals' adaptation, absorption and innovation dynamic capabilities as well as their influence on the performance achieved by these companies. Based on an ambidexterity approach, which points to born globals' need to adopt a double exploration/exploitation function, this study considers these three specific knowledge-based dynamic capabilities analysing their interrelationship taking into account their exploration/exploitation duality. Results from the testing of the structural equation model proposed confirm that network market orientation facilitates the development of dynamic, exploratory capabilities (adaptation and absorption capabilities) in born globals and that these, in turn, influence their capacity to exploit knowledge through innovations, thereby obtaining higher performance."
Keywords: 650; Network market orientation; Dynamic capabilities; International entrepreneurship; Ambidextrism